2012
DOI: 10.1177/0363546512457158
|View full text |Cite
|
Sign up to set email alerts
|

Anteroposterior Thickening of the Femoral Neck With Aging Decreases the “Offset” in Men

Abstract: Our results suggest that, as men age, they develop a relatively thicker femoral neck that could result in increasing cam impingement, which contributes to the known higher prevalence of osteoarthritis in men. This does not seem to be the case in women, as their femoral neck does not appear to grow as quickly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…However, there were differences in the surgical findings between the sexes; males had higher incidence of cam lesions as well as a higher incidence of highgrade cartilage damage requiring microfracture and larger labral tears. As previously mentioned, Johnson et al 10 reported that males develop thicker femoral necks with advanced age, and this may explain why males had a higher incidence of cam lesions. The higher incidence of cam lesions might be the reason for the larger labral tears and higher incidence of chondral damage.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, there were differences in the surgical findings between the sexes; males had higher incidence of cam lesions as well as a higher incidence of highgrade cartilage damage requiring microfracture and larger labral tears. As previously mentioned, Johnson et al 10 reported that males develop thicker femoral necks with advanced age, and this may explain why males had a higher incidence of cam lesions. The higher incidence of cam lesions might be the reason for the larger labral tears and higher incidence of chondral damage.…”
Section: Discussionmentioning
confidence: 83%
“…The investigators reported that females have smaller alpha angles and increased anteversion. In addition, Johnson et al 10 reported that males develop thicker femoral necks with advanced age, which might lead to increased incidence of femoroacetabular impingement (FAI) in male patients over the years.…”
mentioning
confidence: 99%
“…Some studies have postulated that the increased prevalence in athletes is the result of vigorous sports activity in adolescence, predisposing the growing hip to the development of altered morphology [41,42]. Another possibility is that remodeling of the mature hip as a result of activity-related stresses is neither pathological nor unexpected [20]. We do not have additional insight into the etiology of cam FAI based on our methods (a single radiograph in time).…”
Section: Discussionmentioning
confidence: 91%
“…39 Controversy continues as FAI may therefore in some instances be considered the result of ongoing osteoarthritic hip changes. Furthermore Johnson et al, 40 has shown that in males, femoral neck thickening occurs naturally as a result of aging that leads to a progressive 18% decrease in head/neck ratio from ages 20 to 80 years. This is an important source of bias that should be considered especially in studies with predominantly older male populations reporting high rates of CAM-type impingement.…”
Section: Discussionmentioning
confidence: 99%